Integrasi Nilai-nilai Pendidikan Karakter dalam Pembelajaran Pendidikan Agama Islam pada Sekolah Berbasis Boarding School di Indonesia - Abdi, Muhammad Iwan (el Buhuth: Borneo Journal of Islamic Studies, 2021)
ABSTRACT This research, inspired by the publication of the Minister of Education and Culture number 20 of 2018 concerning strengthening character education in formal education units, states that strengthening character education is an educational movement that is the responsibility of each educational unit to strengthen the character or character of students through a balance between Thoughts and sports that involve a partnership of several components, namely between the family education unit and the community, are part of the National Mental Revolution Movement (GNRM). One of the character values ​​that according to the researcher has an important role in shaping the character of students in the Indonesian context is religious values. Indonesia as a country based on God Almighty (read: holding fast to religious values) makes religious values ​​a guide in the life of its people. if it is specified in the implementation of education, then one of the components that play a role in the formation of this character is Islamic Religious Education (PAI). This study aims to determine the form of integration of character education values ​​in PAI learning at boarding school-based schools in Indonesia. Based on the findings and results of the analysis, it can be concluded that there are several character values ​​developed by PAI teachers in learning, namely: religious, honest, literacy, curiosity, communication, social care, environmental care and discipline. activities that are prioritized in its implementation.